1999
DOI: 10.1006/viro.1999.9766
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Circular Single-Stranded DNA Associated with Cotton Leaf Curl Disease in Pakistan

Abstract: Recent reports have suggested that cotton leaf curl virus (CLCuV), a geminivirus of the genus Begomovirus, may be responsible for cotton leaf curl disease in Pakistan. However, the causal agent of the disease remains unclear as CLCuV genomic components resembling begomovirus DNA A are unable to induce typical disease symptoms when reintroduced into plants. All attempts to isolate a genomic component equivalent to begomovirus DNA B have been unsuccessful. Here, we describe the isolation and characterisation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(133 citation statements)
references
References 44 publications
1
131
0
1
Order By: Relevance
“…In summary, evidence provided here and elsewhere indicates that several types of alphasatellite are associated with begomovirus-betasatellite complexes (Briddon et al, 2004;Mansoor et al, 1999). However, a role for alphasatellites in disease aetiology or virulence has not been shown.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In summary, evidence provided here and elsewhere indicates that several types of alphasatellite are associated with begomovirus-betasatellite complexes (Briddon et al, 2004;Mansoor et al, 1999). However, a role for alphasatellites in disease aetiology or virulence has not been shown.…”
Section: Discussionmentioning
confidence: 63%
“…Monopartite begomoviruses are frequently associated with two classes of satellite molecule, referred to as alphasatellites (Briddon et al, 2004;Mansoor et al, 1999) or betasatellites , and thus far are exclusively found in the EH. However, recently alphasatellites have been identified in conjunction with WH bipartite begomoviruses (Paprotka et al, 2010;Romay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Begomoviruses have been reported to be associated with ssDNA satellite molecules and/or satellite-like molecules, namely betasatellites and alphasatellites, respectively (Mansoor et al, 1999;Nawaz-ul-Rehman & Fauquet, 2009;Saunders et al, 2000). The majority of the Old World monopartite begomoviruses co-exist with betasatellites.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller (approx. 1350 nucleotides) single stranded DNA molecule (termed DNA-1) was shown to be associated with CLCuD (Mansoor et al, 1999). This molecule capable of self-replication in plant cells but requiring CLCuV for spread in plants as well as in insect transmission was shown to play no part in inducing symptoms.…”
Section: Cotton Leaf Curl Virusmentioning
confidence: 99%
“…They provide inoculum to the vector for transmitting the same in cotton. There are many ornamental plants and common weeds which have been found infected with whiteflytransmitted geminiviruses (Mansoor et al, 1998;Mansoor et al, 1999). Singh et al, (1994) reported appearance of the CLCuD on the Sidasps, Abutilon indicum, Hibiscus rosa-sinensis, and Althea roses on the basis of visual symptoms.…”
Section: Symptomatology Of Clcudmentioning
confidence: 99%